THE EFFECT OF LIQUIDITY RATIO AND OPERATIONAL EFFICIENCY ON PROFITABILITY WITH CREDIT RISK AS AN INTERVENING VARIABLE - Wijaya, Agung (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: Banks serve a vital function as financial intermediaries by directing public funds into credit allocation. This research investigates how liquidity ratios and operational efficiency influence profitability, with credit risk acting as a mediator, in publicly traded banks in Indonesia from 2018 to 2021. Methods: Employing purposive sampling, the data were analyzed using PLS regression techniques. Findings: The findings reveal that the liquidity ratio significantly impacts credit risk directly, while it does not have a significant direct effect on profitability. Additionally, operational efficiency significantly affects credit risk and also has a direct impact on profitability. Furthermore, credit risk is shown to significantly influence profitability. However, liquidity ratios do not significantly affect profitability through credit risk, nor does operational efficiency have a significant effect on profitability when mediated by credit risk. Paper type: Research paper